A size-controlled green synthesis of silver nanoparticles by using the berry extract of Sea Buckthorn and their biological activities. (26th May 2020) - Wei, Simin; Wang, Yinghui; Tang, Zhishu; Hu, Jinhang; Su, Rui; Lin, Jingjie; Zhou, Tuan; Guo, Hui; Wang, Nan; Xu, Rongrong
Abstract : Herein, by using the Sea Buckthorn berry extract, we present a new eco-friendly approach for green synthesis of AgNPs, which reveal superior antioxidation and anticancer but poor antimicrobial activities. Abstract : Green synthesis of silver nanoparticles (AgNPs) has been extensively studied by using a variety of plant extracts for applications in biomedical sciences and engineering. However, there are no reports on the synthesis of AgNPs by utilizing the berry extract of Sea Buckthorn, which is a traditional Chinese medicine and exhibits a wide spectrum of antioxidant, anti-inflammatory and anticancer activities. In this paper, we report an easy and eco-friendly technique for the preparation of AgNPs using the Sea Buckthorn berry extract under ultrasonic radiation at ambient temperature and the evaluation of both biosynthesis parameters and biological activities. The UV-visible spectrum and dynamic light scattering (DLS) analysis showed that the size of AgNPs was sensitive to the biosynthesis parameters, such as the pH of the extract, material proportion and reaction time, offering a size-controlled synthetic method for AgNPs. The X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and DLS studies showed that the AgNPs (pH 10.0; material proportion 1 : 1; 4 h) had a face-centered cubic (fcc) structure and spherical shape with an average particle size of 27.3 ± 0.2 nm covered by anions, and existed in a monodispersed form with a polydispersity index (PDI) of 0.213. The biosynthesized AgNPs showed potent anticancer activity against human colorectal cancer (HCT116 and SW620), hepatoma cancer (HepG2), breast cancer (MCF-7) and cervical cancer (HeLa) cell lines as well as strong antioxidant activity. The IC50 values for these five cell lines were 8.77, 4.61, 14.59, 16.05 and 27.98 μg mL −1, respectively. However, the biosynthesized AgNPs revealed poor inhibition activities for the growth of E . coli and S . aureus . These results confirmed that the Sea Buckthorn could be a low-cost, nontoxic and eco-friendly natural resource for the synthesis of AgNPs, which might be useful for the development of new alternative antioxidant and anticancer agents in biomedicine.